Identification and character analysis of the Acerentomidae (Protura) of the northeastern Palearctic (Protura: Acerentomidae) - Shrubovych, Julia (Zootaxa, 2014)
This paper is a summary of proturan fauna from Siberia and the Russian Far East, collectively termed the northeastern Palearctic. Special attention is given to the analysis of Acerentomidae, which is extraordinarily diverse in these regions (31 species). A key to species and a brief exposition of distribution of each genus are provided. A redescription of Imadateiella sharovi is presented, additional morphological characters are added for Nipponentomon khabarovskense, N. bidentatum, Yamatentomon yamato and Callientomon chinensis, and additional collection data are given for Y. yamato, C. chinensis, Nipponentomon jaceki and N. nippon. A cladistic analysis is presented of hypothetical relationships among the discussed acerentomid taxa. A scheme for ventral porotaxy is proposed, and the taxonomic importance of porotaxic characters within Acerentomata is discussed. Some biogeographical and phylogenetic considerations are given.